Ingestible sensor capsule with extended battery capacity allows early diagnosis of GI malignancy in comorbid patients with occult bleeding and anemia - Cahyadi, Oscar; Ewald, Peter; Quast, Daniel; Siau, Keith; Uhl, Waldemar; Schmidt, Wolfgang; Torres Reyes, Christian (Endoscopy International Open, 2025)
HemoPill is a commercially available ingestible electronic capsule that detects hematin and blood through photometric measurements. An examination with HemoPill requires no special preparation and can be done bedside. Its major advantage is noninvasive luminal blood detection, requiring only a small amount of blood or hematin (> 20 mL) for a positive result, making it especially suitable in multimorbid and/or geriatric patients not primarily fit for endoscopic diagnostic allowing rapid and uncomplicated bleeding detection.Recent clinical reports showed that HemoPill is useful in stratifying patients with anemia and bleeding in the setting of an Emergency Department. The second generation with an extended battery capacity of 9 hours opens the possibility of detecting blood in the middle and lower gastrointestinal tract.Herein we report another advantage of the extended battery capacity allowing noninvasive bleeding detection in the middle and lower gastrointestinal tract, leading to early endoscopic diagnosis of gastrointestinal malignancies with occult bleeding in comorbid patients with severe anemia.
Keywords: Endoscopy Small Bowel; Small intestinal bleeding; Capsule endoscopy; Small bowel endoscopy